2021
DOI: 10.3390/nu13124324
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Antioxidant Capacity Promotes a Protective Effect against Exacerbated Oxidative Stress in Women Undergoing Adjuvant Treatment for Breast Cancer in a Prospective Study

Abstract: Breast cancer (Bca) is the most common type of cancer among women worldwide, and oxidative stress caused by adjuvant treatment may be decreased by antioxidant intake. The aim of this study is to investigate the associations between Dietary antioxidant Capacity (DaC) and oxidation and antioxidant biomarkers in women undergoing adjuvant treatment (AT) for Bca. This prospective study had a sample of 70 women (52.2 ± 10.7 y). DaC (mmol/g) was calculated using nutritional data obtained from a Food Frequency Questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 65 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…Mechanisms underlying the action of dietary antioxidant capacity have been investigated in previous studies, which showed a significant counteractive effect on systemic oxidative stress and inflammation [53,54]. Mediation analysis found that serum CRP was a mediator of the association between total, dinner or Δ DACs and all-cause mortality risk.…”
Section: Discussionmentioning
confidence: 97%
“…Mechanisms underlying the action of dietary antioxidant capacity have been investigated in previous studies, which showed a significant counteractive effect on systemic oxidative stress and inflammation [53,54]. Mediation analysis found that serum CRP was a mediator of the association between total, dinner or Δ DACs and all-cause mortality risk.…”
Section: Discussionmentioning
confidence: 97%
“…Breast cancer (BC) is a multifaceted condition with varied molecular subtypes and outcomes, accounting for a substantial number of new diagnoses, estimated at around 2.3 million cases [ 1 , 2 , 3 ]. Insufficient nutrition, lack of physical activity, and exposure to pollutants associated with modern lifestyles increase the body’s production of free radicals, causing oxidative stress [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient nutrition, lack of physical activity, and exposure to pollutants associated with modern lifestyles increase the body’s production of free radicals, causing oxidative stress [ 4 , 5 , 6 , 7 ]. Oxidative stress and the generation of reactive oxygen species (ROS) are associated with cancer progression [ 1 , 8 , 9 ]. Oxidative stress is a hallmark of BC, where there is an inequilibrium between the generation of ROS and the body’s ability to counteract them through antioxidant defense mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, one of the main causes of food aversions in response to adjuvant chemotherapy is increased oxidative stress [ 10 ]. We have already demonstrated that diet quality and a diet rich in antioxidants can help mitigate the excess production of reactive oxygen species [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%